Current management of symptomatic vesicoureteral reflux in pediatric kidney transplantation - a European survey among surgical transplant professionals - Zirngibl, Matthias; Weitz, Marcus; Luithle, Tobias; Tönshoff, Burkhard; Nadalin, Silvio; Buder, Kathrin (Pediatric transplantation, 2023)
Background Vesicoureteral reflux (VUR) is common in children and adolescents undergoing kidney transplantation (KTx) and may adversely affect allograft kidney function. Methods To explore the current management of symptomatic native and allograft VUR in pediatric KTx recipients, an online survey was distributed to European surgical transplant professionals. Results Surgeons from 40 pediatric KTx centers in 18 countries participated in this survey. Symptomatic native kidney VUR was treated before or during KTx by 68% of the centers (all/selected patients: 33%/67%; before/during KTx: 89%/11%), with a preference for endoscopic treatment (59%). At KTx, 90% favored an anti-reflux ureteral reimplantation procedure (extravesical/transvesical approach: 92%/8%; preferred extravesical technique: Lich-Gregoir [85%]). Management strategies for symptomatic allograft VUR included surgical repair (90%), continuous antibiotic prophylaxis (51%), bladder training (49%), or noninterventional surveillance (21%). Redo ureteral implantation and endoscopic intervention for allograft VUR were equally reported (51%/49%). Conclusions This survey shows uniformity in some surgical aspects of the pediatric KTx procedure. However, with regard to VUR, there is a significant variation in practice patterns that need to be addressed by future well-designed and prospective studies. In this way, more robust data could be translated into consensus guidelines for a more standardized and evidence-based management of this common condition in pediatric KTx.
Online veröffentlicht: 13. Oktober 2023
Gesehen am 03.01.2024